Conceptual foundations of the People’s Republic of Сhina’s international development assistance policy - Rubo, Olesya P. (Journal of the Belarusian State University. International Relations, 2024)
The People’s Republic of China is a major actor in global international development assistance. This article analyses white papers and other official documents related to China’s international development assistance policy. Through detailed examination, the objectives, principles, and priority areas are identified, highlighting contemporary trend which is shifting from the terms “aid” and “donor – recipient relationships” to “partnership” and “international development cooperation”. It is concluded that China actively employs development assistance as a tool in its foreign policy, enabling it to achieve national goals, increase its political and economic influence in the international arena, strengthen the legitimacy of its actions, and promote the Belt and road initiative and the construction of a global community of shared future.
Keywords: People’s Republic of China; international development assistance; official development assistance; regulatory framework; White paper; Belt and road initiative; global community of shared future